Rapporter - Krogh Groth, Sanne; Krogh, Mads; Leiska, Katharine; Wickström, David-Emil; Fjeldsøe, Michael; Nissen, Peter E.; Foltmann, Niels Bo; Rørdam Larsen, Charlotte; Have, Iben; Kaargaard Nielsen, Steen; Holme Hansen, Thomas (Danish Yearbook of Musicology, 2008)
Research Projects EMS: Two Music Cultures – One Institution. Swedish electro-acoustic music from 1965 to the late 1970s (Sanne Krogh Groth) Hip Hop Culture as Musical Practice: Analyses and Discussions (Mads Krogh) Skandinavische Symphonik im wilhelminischen Kaiserreich (Katharine Leiska) Transformations in Russian Popular Music of the Post-Soviet Era – Case study St Petersburg (David-Emil Wickström) Conferences Zoltán Kodály Symposium, Copenhagen 2007 (Michael Fjeldsøe) Passagen – 18th Congress of the International Musicological Society (IMS), Zurich 2007 (Peter E. Nissen) Digital Editions. Perspectives for Editors and Users, University of Copenhagen, January 2008 (Niels Bo Foltmann) Music, Media & Emotions, University of Aarhus, October 2007 (Charlotte Rørdam Larsen & Iben Have) Sound Art, Auditory Culture, University of Copenhagen, 28–30 November 2007 (Steen Kaargaard Nielsen) Danish Musicological Society, 2007 (Thomas Holme Hansen)